Establishment of Poliovirus Purification Procedure for the Development of Inactivated Polio Vaccine - Pham, Ich Tung; Nguyen, Dang Hien; Trinh, Van Quang; Dang, Mai Dung; Dang, Thi Ngan Ha; Nguyen, Nghia Vu; Truong, Quoc Phong (Old Journal, 2018)
In this paper we present the results of the production of poliovirus I, II and III for studying the purification procedure and the development of inactivated vaccines. The results showed that the ultrafiltration of the poliovirus resulted in the increase of poliovirus density over 80 times; the average recovery yield of 3 types was 93.54%. After ultracentrifugation the average recovery yield of 3 types was achieved as 60.10%. The average recovery yield of 3 poliovirus types after purification through the column chromatography was 91.11 %. Following purification, the poliovirus was inactivated by formalin and the total of antigen titer was highest for Type III (1.54x10^5 DU) and lowest for Type II (5.36x10^4 DU). The properties of post-refined and inactivated poliovirus suspension meet the requirements for producing the bulk of polio vaccines.